Restaurant Taxpayer Billing System at the Medan City Regional Tax and Retribution Management Agency in 2022 - Salimah, Salimah; Harahap , Rahmat Daim (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
In collecting taxes is a major aspect and must be considered by the government at all levels of central and local. Because tax collection in general is an effort where taxpayers must pay their taxes, their tax debts, pay off collection fees and arrange and warn to take billing actions such as forced letters, confiscate, and sell confiscated goods. In this study, conducted on the restaurant tax collection system at the Medan City BPPRD, this study aims to determine whether the restaurant tax billing system carried out at the Medan City BPPRD is in accordance with regulation No.19 of 2000. This research includes qualitative descriptive research. The research subject is the Medan City BPPRD Office. The restaurant tax imposition rate at the Medan City Tax and Levy Management Agency is 10% (ten percent) and the procedure for collecting restaurant taxes at the Medan City Tax and Levy Management Agency uses one system, namely the Self Assessment System.